Interspecific interactions regulate plant reproductive allometry in cereal–legume intercropping systems. Issue 11 (22nd August 2021) - Gaudio, Noémie; Violle, Cyrille; Gendre, Xavier; Fort, Florian; Mahmoud, Rémi; Pelzer, Elise; Médiène, Safia; Hauggaard‐Nielsen, Henrik; Bedoussac, Laurent; Bonnet, Catherine; Corre‐Hellou, Guénaëlle; Couëdel, Antoine; et al.
Abstract: Calls for the application of ecological principles in agriculture have gained momentum. Intercropping systems are designed by growing two, or more, annual crop species in the same field, aiming for a better resource use efficiency. However, assembly rules for their design are lacking. Notably, it is unknown whether species performances are maximized during both the vegetative and reproductive phases given the sensitivity of reproductive allocation rules to resource limitation. Interestingly, ecological theory provides expectations regarding putative invariance of plant reproductive allometry (PRA) under non‐limiting conditions for plant growth. Here we examined whether and how PRA changes in response to plant–plant interactions in intercropping systems, which can inform both ecological theory and the understanding of the functioning of intercropping systems. We analysed a dataset of 28 field cereal–legume intercropping trials from various climatic and management conditions across Western Europe. PRA was quantified in both mixing and single‐species situations. Plant reproductive allometry was positively impacted in specific management conditions, leading to a greater increase in yield for a given increase in plant size. Variations in PRA were more beneficial to legumes grown in unfertilized mixtures, which explains their use as a key component in actual intercropping systems. The response for cereals was similar but less pronounced in magnitude, and was greater under resource‐limiting conditions. Focusing on intercropping conditions, hierarchical competition (indicated by biomass difference between intercropped species) appears as a strong driver of the reproductive output of a given species. Synthesis and applications . Plant reproductive allometry (PRA) behaves in crop species in the same way as it does in wild species. However, contrary to theoretical expectations about an overall invariance of PRA, we highlighted taxon‐specific and context‐dependent effects of plant–plant interactions on PRA. This systematic deviation to PRA expectations could be leveraged to cultivate each species up to its reproductive optimum while accounting for the performance of the other, whether farmer's objective is to favour one species or to reach an equilibrium in seed production. Sowing density and cultivar choice could regulate the biomass of each component, with specific targets derived from allometric relationships, aiming for an optimal reproductive allocation in mixtures. Abstract : Plant reproductive allometry (PRA) behaves in crop species in the same way as it does in wild species. However, contrary to theoretical expectations about an overall invariance of PRA, we highlighted taxon‐specific and context‐dependent effects of plant–plant interactions on PRA. This systematic deviation to PRA expectations could be leveraged to cultivate each species up to its reproductive optimum while accounting for the performance of the other, whether farmer's objective is to favour one species or to reach an equilibrium in seed production. Sowing density and cultivar choice could regulate the biomass of each component, with specific targets derived from allometric relationships, aiming for an optimal reproductive allocation in mixtures.